Exploring The Relationship Between Sufism and Hadith: A Qualitative Analysis of Key Narrations and Interpretations - Hasan Mud’is (Diroyah : Jurnal Studi Ilmu Hadis, 2023)
This study examines how Sufi scholars have utilized Hadith to develop a framework for their spiritual practices, including pursuing inner knowledge and cultivating spiritual states. Additionally, it aims to analyze key Hadith narrations central to the development of Sufi thought, such as those concerning the nature of God, the role of Prophet Muhammad, and the path to spiritual enlightenment. This study utilizes a qualitative research approach to comprehensively analyze key Hadith narrations in Sufi literature and explore the relationship between Sufism and Hadith. The methodology involves a thorough literature review of primary and secondary sources, including Hadith collections and commentaries, works of Sufi scholars, and relevant academic studies. Qualitative data analysis techniques, such as content analysis and thematic coding, are employed to identify key themes and patterns in the Hadith narrations and Sufi interpretations. The study demonstrates that the teachings of Sufism are rooted in the prophetic tradition and can be referenced in various Hadiths of the Prophet that discuss the practice of Sufism. The Hadiths emphasize the importance of worshipping God to the best of one’s ability (ihsan), purifying oneself from things that can defile the heart and hinder the light of God (tazkiyat al-nafs), and practicing zuhud or detachment from excessive love for the material world. Sufis strive to find the basis of these Sufi teachings through esoteric interpretation of these Hadiths. This effort is not only essential for integrating Hadiths and Sufi teachings but also for seeking the Prophet’s most profound insights and teachings